Development and performance testing of 'Comb Separator', a novel sewer overflow screening device. (2015) - Aziz, Md. Abdul; Imteaz, Monzur A.; Rasel, H.M.; Phillips, Donald
Rivers and creeks receive a lot of sewer solids due to sewer overflow. This overflow causes a serious concern for the environment, aesthetics and public health. To manage such sewer overflow, different types of screening device were developed. The initial expense, maintenance costs, poor sewer capture efficiency and blinding on the screen were discussed as the limitations of these overflow devices. Most screens had electro-mechanical systems that were expensive, complex and caused concern for possible malfunctions in unstaffed remote locations. Consequently, a novel sewerage overflow device 'Comb Separator' was conceived, developed and tested. Optimum criteria were achieved for the device using trial and error method; robustness of the experimental set-up was tested to reproduce consistent results. There was minimal blockage on the screen and higher capture efficiency than Hydro-JETTM. The 'Comb Separator' has a good application potential to improve the sewer solids capture in the urban sewerage system.